Faktor-Faktor yang Memengaruhi Financial Distress pada Perusahaan Consumer Goods di Indonesia - Dian Safitri P. Koseomasari; Harsuti Harsuti; Novanda Nur Huda (Faculty of Economics and Business, Universitas Stikubank, 2021)
The purpose of this study was to analyze the effect of profitability, leverage and liquidity on financial distress. The difference from previous research is the use of financial distress measurement using interest coverage ratio (ICR) which is simpler than Altman Z-score. ICR measures bankruptcy by assessing the amount of risk a company poses with debt that the company's operating income can bear. The population of this study is consumer goods listed on the Indonesia Stock Exchange amounting to 55 companies. Determination of research samples using purposive sampling and obtained 13 sample companies. The data in this study were tested by multiple regression analysis techniques panel data. Testing is carried out using the common model and has passed the classical assumption test. The findings of this research indicate that profitability and leverage have a significant positive effect on financial distress. Meanwhile, liquidity has a significant negative effect on financial distress.